2015
DOI: 10.1002/cbic.201500425
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I/II), α/β‐Synuclein and Amyloid‐β: Menage à Trois?

Abstract: Copper binding to α-synuclein (aS) and to amyloid-β (Ab) has been connected to Parkinson's and Alzheimer's disease (AD), respectively, because Cu ions can modulate the peptide aggregation, and these Cu ⋅ peptide complexes can catalyse the production of reactive oxygen species (ROS). In a significant proportion of AD brains, aggregation of aS and Ab has been detected, and it was proposed that Ab and aS interact with each other. Thus, we investigated the potential interactions of Ab and aS through their binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 59 publications
2
50
1
3
Order By: Relevance
“…Exchange between protein and metal has been observed in studies that found MTs prevented copper-induced aggregation of amyloid beta peptide or alpha-synuclein (Meloni et al, 2008; Meloni and Vašák, 2011; De Ricco et al, 2015b). The MT gene promoter contains a metal response element (Richards et al, 1984; Sadhu and Gedamu, 1989; West et al, 1990; Pountney et al, 1995), although the MT-3 isoform does not show metal inducibility (Faller, 2010).…”
Section: Metallothioneinsmentioning
confidence: 95%
See 1 more Smart Citation
“…Exchange between protein and metal has been observed in studies that found MTs prevented copper-induced aggregation of amyloid beta peptide or alpha-synuclein (Meloni et al, 2008; Meloni and Vašák, 2011; De Ricco et al, 2015b). The MT gene promoter contains a metal response element (Richards et al, 1984; Sadhu and Gedamu, 1989; West et al, 1990; Pountney et al, 1995), although the MT-3 isoform does not show metal inducibility (Faller, 2010).…”
Section: Metallothioneinsmentioning
confidence: 95%
“…More recently, overexpression of MT-1 in a mouse model of AD promoted reversal in behavioral symptoms of disease and more inert soluble amyloid species (Manso et al, 2016). Indeed, extracellular alpha-synuclein inhibits β-amyloid plaque formation (Bachhuber et al, 2015), a process that may also be influenced by extracellular MT binding (De Ricco et al, 2015b). Further, in a mouse model of AD, MT-3- and MT-1/2-deficient mice had lower plaque burdens and mortality, and performed better in behavioral tests (Manso et al, 2012a,b).…”
Section: Oxidative Stress and Neuroinflammationmentioning
confidence: 99%
“…[67] Theconnection with DA toxicity comes from studies showing that elevation of DA levels induces aSyn oligomers and increase nigrostriatal degeneration. [74][75][76][77][78] Assuming that these reactions will be particularly important intracellularly in the case of cytosolic DA excess and in oxidative stress conditions, or in the extracellular space when damaged neurons release large amounts of DA,t he starting form of the metal ion will be oxidized, and this governs the interaction with the peptide. [69] Ther eactivity of metal ions towards catecholamines is modulated by binding to coordinating ligands and their association to peptides and proteins involved in neurodegeneration.…”
Section: Metal-catalyzed Dopamine Oxidationmentioning
confidence: 99%
“…Dieser Effekt wird durch spezifische Chelatoren der beiden Metallionen vollständig unterdrückt. [74][75][76][77][78] Wirnehmen an, dass diese Reaktionen intrazellulärbesonders im Falle eines DA-Überschusses im Cytosol und unter oxidativen Stressbedingungen bedeutsam werden, extrazellulär, wenn geschädigte Neuronen große Mengen an DA freisetzen. [68] Im Zuge der Redoxreaktionen, die durch Metallionen an DA ausgelçst werden, kann eine Reihe mçglicherweise toxischer Verbindungen wie DASQ,D AQ,O 2 À ,H 2 O 2 und Hydroxylradikale durch komplexe Kettenreaktionen entstehen.…”
Section: Metallkatalysierte Dopaminoxidationunclassified